Carbon fiber permeability characterization using VARTM process. (2021) - Gajjar, Tushar; Shah, Dhaval B.; Joshi, Shashikant J.; Patel, K.M.
Abstract: The vacuum assisted resin transfer moulding (VARTM) process is extensively used for the fabrication of composite parts. The different process parameters are involved during composite manufacturing in the VARTM process. In this paper, flat plates have been fabricated with different thickness from carbon fiber reinforced polymer (CFRP) and epoxy resin along with hardener using VARTM process. The total number of layers of CFRP composite has been considered as 4, 8, and 12 in the experimentation. The digital camera has been used to record images and the resin flow during mould filling process. The permeability has been calculated along the length of the component for each case based on Darcy's law. The variation in the permeability along with the mould filling time and infusion area has been observed for each fabricated composite plates. The permeability is maximum at resin inlet and gradually decreases along with the length and found minimum at resin outlet position for all fabricated CFRP flat plates. The time taken for covering 67% of the infusion area is approximately equal to the last 33% area during the mould filling in the VARTM process.